Connecting with pre-service teachers’ perspectives on the use of digital technologies and social media to teach socially relevant science - Ronicka Mudaly; Kathleen Pithouse-Morgan; Linda van Laren; Shakila Singh; Claudia Mitchell (Perspectives in Education, 2015)
As an interdisciplinary team of educational researchers we explored pre-service science teachers’ perspectives on using digital technologies and social media to address socially relevant issues in science teaching. The rationale for teaching socially relevant science was embedded in the concept of renaiscience, thus underscoring the need for science to be perceived as a human activity. We drew on generational theory to consider the educational significance of digital technologies and social media. Two different activities were used to elicit the pre-service science teachers’ perspectives. First, we invited them to reflect on a digital animation that we had produced, and they highlighted the advantages of digital animation as a medium to communicate a socially relevant message more appealingly to the Millennial generation. We then engaged these pre-service teachers in a structured concept-mapping activity to consider how digital technologies and social media might be used to address social challenges in South Africa. They drew our attention to the affordances of digital technologies and social media as a means to facilitate critical thinking, cater for diverse learning styles, and make high-quality scientific knowledge more accessible. They highlighted that teaching socially relevant science using digital resources can be cheap, convenient, collaborative, and creative.